Pemberdayaan Masyarakat Melalui E-Branding Destination Berbasis Kearifan Lokal Dalam Revitalisasi Kawasan Wisata Putri Maron - Annisa Purnadita; Amelia Reza Artanti; Antin Tri Wahyuni; Achmad Mufti Fauzi; Sri Untari (Politeknik Siber Cerdika Internasional, 2023)
Putri Maron tourism is very popular among mothers and teenagers in Trenggalek Regency. However, it has been inactive due to the Covid-19 pandemic. The Covid-19 pandemic has greatly impacted the lives of people around the tourist sites. So, now the condition of the Putri Maron tourist area has become unkempt. Through this, local residents really hope that tourism will return to its former life. The purpose of writing this article is as a form of concrete evidence of community service activities that have been carried out by one of the community service teams at the State University of Malang. In this study, one of the quantitative research methods, namely the survey method, was carried out. Based on the distribution of survey questionnaires that have been carried out, many of the residents agree to the e-branding of Putri Maron tourism destination. In addition, the results of service activities can be achieved through efforts: First, the socialization of Putri Maron tourism revitalization. Second, repairing facilities by working together with local residents. Third, the introduction of objects focused on three iconic places in Depok Village so as to produce an e- branding video product for Putri Maron tourism. This activity is expected to be able to empower and drive the community's economy, and this revitalization can be one of the ways to revive the role and function of an area so that it can develop even more.